Implementation of Spiritual Leadership Style in an Effort to Improve Employee Performance: (A Case Study of RM. Pangestu Special Lalapan Jember) - Rachmat Ramadhani Pangestu; I Ketut Mastika, I Ketut Mastika (Rumah Jurnal, University of Jember, 2025)
This study aims to analyze the implementation of spiritual leadership in an effort to improve employee performance in RM. Pangestu Special Lalapan mention of the Jember. The background of this research is based on the increasingly fierce competitin in the culinary business in Jember Regency, especially in the typical food business sector. RM. Pangestu Special Lalapan, which has been established since 2001, applies spiritual values as part of its human resource management strategy to create a harmonious and productive work environment. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, documentation of owners, HR managers, employees, and costumers. The main theory used is Spiritual Leadership Theory by Fry et al. which includes three main dimensions, namely: vision, altruistic love, and faith/hope.